Perancangan User Interface Pada Website Organisasi Kemahasiswaan di Fakultas Teknik Universitas Negeri Yogyakarta Dengan Pendekatan Design Thinking - Muhammad Gizka Setiawan; Nurkhamid; Ratna Wardani (Journal of Information Technology and Education (JITED), 2023)
This study aims to design a User Interface on the student organization's website as a support for the convenience of Student Organizations of the Faculty of Engineering, UNY in terms of organizing activities. Based on previous research, the creation of the SI ORMAWA website was not tested on the User Interface that was developed. So this raises the problem that the existing User Interface does not suit the user's needs. The subjects of this research were the 2022 Faculty of Engineering UNY Ormawa. This research was conducted in several stages using the design thinking method. In the process, design thinking creates an understanding of the user's needs and the steps taken to achieve the user's goals as well as the process of empathizing with the user. The stages of the design thinking process carried out are empathy to produce empathy maps, define to produce user personas, ideas to produce user goals and flows, prototypes to produce low and high fidelity prototypes and finally testing using Usability Testing. This study uses Usability Testing with the Single Ease Questions (SEQ) and System Usability Scale (SUS) methods. In the SEQ results the user's response has three values, namely 5 (quite easy) 2%, 6 (easy) 11% and 7 (very easy) 87% on the Likert scale and the SUS results get Acceptable results with a value of 84.5.